Building resilience of street-connected children during COVID-19: turning rights into practices through CINI method - Bhattacharyya, Debapriya; Chakraborty, Swati (Frontiers in Public Health, 2024)
This article examines the methods and opportunities for street-connected children's (SCC's) meaningful participation in health, nutrition, education and protection services and policies that recognize their agency and are aligned with General Comment No. 21 (GC21) to the United Nations Convention on the Rights of the Child (UNCRC) on Children in Street Situations (UNCRC, 1989). Child in Need Institute (CINI) applied participatory approaches to practice, research, decision-making, and policy development; thus, facilitating children in the process of systematically gathering information with their peers, identifying key issues and problems faced by SCC, and securing support from duty bearers including healthcare providers that were required for the survival within their situations. Drawing on the approach undertaken and the tools used in the participatory research and advocacy, this article reflects upon the processes and strategies that worked out in facilitating SCC's ability to exercise agency and resilience through evidence generation and advocacy during COVID-19 and the associated lockdown and beyond.